2019
DOI: 10.3390/cancers11121936
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Adenomas and Invasiveness from Anatomo-Surgical, Radiological, and Histological Perspectives: A Systematic Literature Review

Abstract: Invasiveness in pituitary adenomas has been defined and investigated from multiple perspectives, with varying results when its predictive value is considered. A systematic literature review, following PRISMA guidelines, was performed, searching PubMed and Scopus databases with terms that included molecular markers, histological, radiological, anatomical and surgical data on invasiveness of pituitary adenomas. The results showed that differing views are still present for anatomical aspects of the sellar region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 175 publications
(255 reference statements)
1
42
0
5
Order By: Relevance
“…These results suggest that decreased expressions of MSH6/2 were partially involved in the molecular mechanism of invasive PAs. On the other hand, recent reports showed that since the introduction of endoscopy in transsphenoidal surgery, surgeons can distinguish between invasive and non-invasive by directly visualizing the medial wall of the cavernous sinus (MWCS) [28]. It is therefore important to take a visual inspection into account, but a limitation of this study is that we could not consider it in this study because of the lack of available data in our database.…”
Section: Discussionmentioning
confidence: 97%
“…These results suggest that decreased expressions of MSH6/2 were partially involved in the molecular mechanism of invasive PAs. On the other hand, recent reports showed that since the introduction of endoscopy in transsphenoidal surgery, surgeons can distinguish between invasive and non-invasive by directly visualizing the medial wall of the cavernous sinus (MWCS) [28]. It is therefore important to take a visual inspection into account, but a limitation of this study is that we could not consider it in this study because of the lack of available data in our database.…”
Section: Discussionmentioning
confidence: 97%
“…Many different molecular changes, different regulatory layers, and signaling pathways play a role in acquisition of invasive phenotype by the cells [ 16 ]. Comparing the results of different studies is also difficult due to slightly different criteria for determining the status of invasive growth used by various researchers [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite their benign nature, PA often shows invasive growth. Invasive PAs are aggressive and result in high mortality because medical and radiation therapies are either partially or completely ineffective [ 2 ]. Therefore, understanding the molecular pathogenesis of the invasive PA and discovering novel biomarkers and therapeutic targets would facilitate early detection, prognosis, and improve patient survival.…”
Section: Introductionmentioning
confidence: 99%